EMPOWERING THE MEUNASAH ALUE VILLAGE COMMUNITY IN FLOOD DISASTER MITIGATION THROUGH ENVIRONMENTAL EDUCATION AND ACTION IN MUARA DUA DISTRICT, LHOKSEUMAWE CITY." - Adnan; Aiyub; Muhammad Roni; Munardi; Maisyura (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2025)
Flooding is a natural disaster that frequently affects coastal areas in Aceh, including Meunasah Alue Village in Muara Dua District, Lhokseumawe City. This condition is caused by high rainfall, suboptimal drainage systems, and low public awareness of environmental cleanliness. This community service activity aims to increase community capacity and awareness in flood mitigation through participatory-based environmental education and action programs. The implementation method uses the Participatory Action Research (PAR) and Community-Based Disaster Risk Reduction (CBDRR) approaches that directly involve the community in the planning, implementation, and evaluation of activities. The program was implemented for three months through stages of flood mitigation education, environmental actions (cleaning ditches, planting vegetation, and creating biopores), and the formation of Village Flood Alert Groups (KSBD). The results of the activity showed a 38% increase in community understanding, a decrease in inundation points from 14 to 6 points, and increased active participation of residents in maintaining environmental cleanliness. In addition to the physical impact, this activity also strengthened collective awareness, social solidarity, and coordination between the community and the village government. Thus, community empowerment through environmental education and action has proven effective in building community resilience to flood risks at the local level and can be used as a model for replication in other areas with similar characteristics.